Eighth grade mathematical achievements: qualitative and quantitative aspects - Sičiūnienė, Viktorija; Dargytė, Janina (Lietuvos matematikos rinkinys, 2013)
This paper presents systematic and classified achievements of eighth grade students’ in the field of algebra and functions. The authors analyze different student skills of satisfactory, basic and advanced achievement levels in particulars themes: expressions, equations, inequalities, simulation and proportionality. Author’s suggestions on how to improve the curriculum are based on the qualitative analysis of the tasks and the statistical analysis of students’ work. Data collect from 8904 country’s students test books and analyze 134 tasks. The authors would like to thank the National Examination Centre for access to the student database.
Keywords: algebra; functions; modern test theory; constructive abilities; achievement levels; reproductive abilities; standardized program